Functional Theory in Change of Geographical Form: Relevance and Importance: Bhaugolik svaroop ke parivartan mein kriyaasheelata siddhaant: praasangikata evan mahatv - Maurya, Dr. Arun Kumar (International Journal of Research in Informative Science Application & Techniques (IJRISAT), 2020)
From the time the earth came into existence till the present time, there is a continuous change in the geographical form. Activity is the main reason for this change. It is because of activity that the entire universe including the earth is balanced. Change is the law of nature, so action is an important part of applying the law.Creation of the universe due to the activity of nature, Earth coming into existence, day and night, weather change, climate creation, due to internal forces, formation of continents, oceans, mountains, plateaus, plains, various landforms due to external forces Formation and deterioration of land, origin of life, formation of minerals, origin of rivers, streams, population change, development and destruction of civilizations, cities, villages, origin of cultural elements, diffusion of innovations, etc. keep on changing in geographical forms.Change is both positive and negative. Now nature changes according to its rules, then with creativity it tries to keep balanced in the earth's ecosystem. This change is positive in future. When human activity increases indiscriminately in the cultural elements, then there is a negative change in the geographical form.It causes local and regional and global problems like pollution, climate change, global warming, resource crisis, food crisis, rapid population growth etc. The purpose of this research paper is to make an objective evaluation of the changes taking place in the geographical form and try to understand the interrelationship of the changes from a scientific point of view. Key words: reactivity, universe, change, internal force, landform, population change, cultural element, innovation, stream, civilization, city.